2013
DOI: 10.1093/nar/gkt796
|View full text |Cite
|
Sign up to set email alerts
|

The head module of Mediator directs activation of preloaded RNAPII in vivo

Abstract: The successful synthesis of a transcript by RNA polymerase II (RNAPII) is a multistage process with distinct rate-limiting steps that can vary depending on the particular gene. A growing number of genes in a variety of organisms are regulated at steps after the recruitment of RNAPII. The best-characterized Saccharomyces cerevisiae gene regulated in this manner is CYC1. This gene has high occupancy of RNAPII under non-inducing conditions, defining it as a poised gene. Here, we find that subunits of the head mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Recent results in yeast have shown that TFIIH-dependent pol II CTD phosphorylation contributes to, but is not required for, the disruption of Mediator–pol II contacts at the promoter 83,84 . Whereas promoter-proximal paused pol II does not appear to be a common regulatory intermediate in yeast 85 , these and other 86 findings suggest a conserved role for Mediator in regulation of pol II promoter escape.…”
Section: Mediator Roles In Pol II Transcriptionmentioning
confidence: 57%
“…Recent results in yeast have shown that TFIIH-dependent pol II CTD phosphorylation contributes to, but is not required for, the disruption of Mediator–pol II contacts at the promoter 83,84 . Whereas promoter-proximal paused pol II does not appear to be a common regulatory intermediate in yeast 85 , these and other 86 findings suggest a conserved role for Mediator in regulation of pol II promoter escape.…”
Section: Mediator Roles In Pol II Transcriptionmentioning
confidence: 57%
“…In Saccharomyces cerevisiae, Mediator subunits Med18, Med19, and Med20, which activate the cytochrome c 1 (CYC1) gene in response to oxidative stress, are required for cell viability (17). Med17 links transcription and DNA repair by facilitating the recruitment of the Rad2/XPG endonuclease to transcribed genes during exogenous genotoxic stress (18).…”
mentioning
confidence: 99%
“…Therefore, in low-oxygen conditions (hypoxic growth), Rox1p is not expressed, and hypoxia-related genes are upregulated (reviewed by Siso et al [ 86 ]). In our study, melatonin downregulated genes related to aerobic conditions in non-stressed cells (mitochondrial or nonmitochondrial) that are targets of Hap1p ( NDE1 , CYC1 but also CIR2 and CLD1 ), Hap2/3/4/5 complex ( COX5A , COX4 but also INH1 ) or both factors ( CYT1 , RIP1 ) ( Figure 7 , Dataset S1 ) [ 79 , 87 ].…”
Section: Resultsmentioning
confidence: 99%